2009
DOI: 10.1007/s12603-009-0214-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Mini Nutritional Assessment short-form (MNA®-SF): A practical tool for identification of nutritional status

Abstract: The newly revised MNA-SF is a valid nutritional screening tool applicable to geriatric health care professionals with the option of using CC when BMI cannot be calculated. This revised MNA-SF increases the applicability of this rapid screening tool in clinical practice through the inclusion of a "malnourished" category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
1,106
0
74

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,557 publications
(1,190 citation statements)
references
References 32 publications
10
1,106
0
74
Order By: Relevance
“…The review evaluated nutrition screening tools used for older adults in the community and reported that the MNA ® -SF was the most appropriate nutrition screening tool for identification of malnutrition risk in community living older adults (>65 years) because of it has demonstrated high sensitivity and specificity (Phillips et al, 2010). The MNA ® -SF, which consists of 6 items (Rubenstein et al, 2001) was derived from the 18-item full MNA ® (Kaiser et al, 2009;Rubenstein et al, 2001). Ease of use and quick screening is highly favourable to ensure wide acceptance among health care personnel.…”
Section: Nutrition Screening Tools Used In the Studiesmentioning
confidence: 99%
“…The review evaluated nutrition screening tools used for older adults in the community and reported that the MNA ® -SF was the most appropriate nutrition screening tool for identification of malnutrition risk in community living older adults (>65 years) because of it has demonstrated high sensitivity and specificity (Phillips et al, 2010). The MNA ® -SF, which consists of 6 items (Rubenstein et al, 2001) was derived from the 18-item full MNA ® (Kaiser et al, 2009;Rubenstein et al, 2001). Ease of use and quick screening is highly favourable to ensure wide acceptance among health care personnel.…”
Section: Nutrition Screening Tools Used In the Studiesmentioning
confidence: 99%
“…According to current ESPEN Guidelines for Nutrition Screening (10), all hospitalized patients should be screened regularly for malnutrition with a validated tool (11)(12)(13)(14). Malnutrition screening offers a simple and rapid process conducted by nurses or healthcare teams or patients (as self-screening) (15).…”
Section: Introductionmentioning
confidence: 99%
“…O estado nutricional é classificado de acordo com a soma obtida em cada item, em três escores: desnutrição (0 a 7 pontos); risco de desnutrição (8 a 11 pontos) e estado nutricional normal (12 a 14 pontos) [19].…”
Section: Métodosunclassified